2023
DOI: 10.5772/intechopen.109389
|View full text |Cite
|
Sign up to set email alerts
|

Frontier Electrospun Fibers for Nanomedical Applications

Abstract: Nanofibers fabrication nowadays has become unimaginable without mentioning or research involving the technique of electrospinning. Due to the vast possibilities that this technique offers in regard to nanofibers morphology, nanofibrous architecture, and application perspective, it has become the main interest of many scientists with various expertise profiles. Electrospun nanofibers are advantageous over conventional fibers due to their lightweight, high surface-to-volume ratio, adjustable fiber diameter/morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 120 publications
0
7
0
Order By: Relevance
“…The present results were in total agreement with those reported in the literature. For instance, the bioactive molecules (BAMs) were efficiently released from the electrospun nanofibers via the so-called burst effect [ 86 , 87 ]. Moreover, in such materials, the BAM release rate could be controlled by the properties of the polymer such as hydrophilic/hydrophobic nature, biodegradability, solubility, stability, BAM distribution, micro-structure, and morphology of fibers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The present results were in total agreement with those reported in the literature. For instance, the bioactive molecules (BAMs) were efficiently released from the electrospun nanofibers via the so-called burst effect [ 86 , 87 ]. Moreover, in such materials, the BAM release rate could be controlled by the properties of the polymer such as hydrophilic/hydrophobic nature, biodegradability, solubility, stability, BAM distribution, micro-structure, and morphology of fibers.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in such materials, the BAM release rate could be controlled by the properties of the polymer such as hydrophilic/hydrophobic nature, biodegradability, solubility, stability, BAM distribution, micro-structure, and morphology of fibers. In addition, the mechanisms involved in the BAM release profiles include diffusion, swelling, diffusion and degradation [ 87 ]. Previously, Taepaiboon et al investigated the release profile of retinoic acid-loaded electrospun cellulose acetate nanofiber mats [ 88 ] and demonstrated that the retinoic acid-loaded fiber mats exhibited a smoother burst release, i.e., a gradual increase in the cumulative release of retinoic acid over 6 h with the maximum retinoic acid released about 34%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the ways to control the delivery of incorporated compounds in electrospun fibers is through the variety of the electrospinning technique, including: blend, emulsion, coaxial, triaxial, or multiaxial electrospinning, side-by-side electrospinning, drug-loaded nanocarriers (nanoparticles, nanotubes, microspheres, liposomes, etc.) electrospinning, as well as post-surface modifications [ 28 , 29 ]. Depending on the fabrication technique, the globular protein unfolds in the high quality solvent, while the active compound is: (1) added directly in the solution (blend electrospinning); (2) dissolved in the shell or the core solution together with additional polymer (coaxial electrospinning); (3) dissolved in the emulsion as the inner phase (emulsion electrospinning); (4) loaded in a separate nanocarrier and then within the plant protein nanofiber; or (5) added after electrospinning through surface functionalization [ 19 ].…”
Section: Electrospinning Of Plant Protein Fibers—modes and Purposesmentioning
confidence: 99%
“…The fabrication process is responsible for the fiber morphology or fibrous structure, which are both important in the design of the drug pace release mechanism. Another important factor is the electrospun fiber composition that includes both type of polymers used as well as drug properties (i.e., hydrophobic and hydrophilic) [ 28 , 29 ]. Depending on the final product’s therapeutic function, the release of the drug can be permediated in several modalities including: immediate or burst release (within several hours) [ 30 ], prolonged or sustained (it may take days to years) [ 31 ], and on-demand delivery or triggered by external stimuli (i.e., pH, temperature, light, magnetic field, etc.)…”
Section: Electrospinning Of Plant Protein Fibers—modes and Purposesmentioning
confidence: 99%